2021
DOI: 10.3389/fnagi.2021.735508
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Biomarkers Predicting the Efficacy of Multimodal Rehabilitative Intervention in the Alzheimer’s Dementia Continuum Pathology

Abstract: In this work we aimed to identify neural predictors of the efficacy of multimodal rehabilitative interventions in AD-continuum patients in the attempt to identify ideal candidates to improve the treatment outcome. Subjects in the AD continuum who participated in a multimodal rehabilitative treatment were included in the analysis [n = 82, 38 Males, mean age = 76 ± 5.30, mean education years = 9.09 ± 3.81, Mini Mental State Examination (MMSE) mean score = 23.31 ± 3.81]. All subjects underwent an MRI acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Even respondents who do not use it are interested and see this as a useful tool supporting clinical and research settings. This result may be explained by the growing body of evidence supporting the use of neuroimaging biomarkers throughout the dementia continuum (MCI 75 ) and care pathway including diagnosis, 76 progression, 77 and predicting treatment response 78 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even respondents who do not use it are interested and see this as a useful tool supporting clinical and research settings. This result may be explained by the growing body of evidence supporting the use of neuroimaging biomarkers throughout the dementia continuum (MCI 75 ) and care pathway including diagnosis, 76 progression, 77 and predicting treatment response 78 …”
Section: Discussionmentioning
confidence: 99%
“…This result may be explained by the growing body of evidence supporting the use of neuroimaging biomarkers throughout the dementia continuum (MCI 75 ) and care pathway including diagnosis, 76 progression, 77 and predicting treatment response. 78 Neither peripheral nor genetic biomarkers are currently reported as being used for clinical purposes. A barrier to the clinical implementation of peripheral biomarkers might be the lack of adequate centers and standardized protocols for sample processing.…”
Section: Biomarker Purposesmentioning
confidence: 99%
“…Identifying factors influencing rehabilitation response in chronic neurological diseases is a relevant field of investigation paving the way for treatment personalization and customization 1,2 , with the potential to maximize efficacy. Previous studies revealed the role of demographics, clinical conditions and psychosocial variables in modulating rehabilitation outcomes [1][2][3][4] .…”
mentioning
confidence: 99%
“…Identifying factors influencing rehabilitation response in chronic neurological diseases is a relevant field of investigation paving the way for treatment personalization and customization 1,2 , with the potential to maximize efficacy. Previous studies revealed the role of demographics, clinical conditions and psychosocial variables in modulating rehabilitation outcomes [1][2][3][4] . Besides these factors, the latest evidence supported the role of life-long stimulating activities in influencing patients' attitudes and responses to nonpharmacological interventions in neurological disorders [4][5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Research on neurodegeneration and aging has highlighted the importance of identifying objective measures of biological processes that characterize medical states and clinical outcomes (Belleville & Bherer, 2012;di Tella et al, 2021;Horvath et al, 2018;Meghdadi et al, 2021;Nuzzo et al, 2014;Parnetti et al, 2019;Poil et al, 2013;Solís-Vivanco et al, 2015). Biomarkers (Strimbu & Tavel, 2010) of neurocognitive dysfunctions are commonly obtained using neuroimaging techniques, such as functional magnetic resonance (fMRI) and electroencephalography (EEG).…”
Section: Electrophysiological Signatures Of Metacognitive Processesmentioning
confidence: 99%